The Influence af Shopping Lifestyle and Korean Brand Ambassadors on Impulsive Buying and Brand Awareness - Muhammad Rafli Azlam Azzuhri; Suhermin Suhermin (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to determine and analyze the effect of shopping lifestyle and Korean brand ambassadors on impulsive buying with intervening brand awareness on student users of Scarlett Whitening in Surabaya. This research employed a quantitative methodology. The population under investigation was individuals who utilized Scarlett Whitening in Surabaya, which was impossible to determine. The sample size was calculated using the Lemeshow formula, with 97 participants. The variables examined in this study were Shopping Lifestyle, Korean Brand Ambassador, Brand Awareness, and Impulsive Buying. The data sampling technique used in this study was a questionnaire. The data analysis method in this study used the SmartPLS 3.0 application by testing the path diagram, outer model test, inner model test, and hypothesis testing.The results of this study indicated that shopping lifestyle directly or through brand awareness has a positive and significant effect on impulsive buying among students who use Scarlett Whitening in Surabaya. Meanwhile, brand awareness affected impulsive buying for students who use Scarlett Whitening in Surabaya. The Korean brand ambassador variable directly and through brand awareness affected impulsive buying for students who used Scarlett Whitening in Surabaya.